Law Enforcement Against The Crime Of Human Trafficking At Line Two, Poros Samarinda-Tenggarong - Rahman Risanto; La Syarifuddin; Rini Apriyani (Universitas PGRI Madiun, 2021)
Indonesia has provided a legal basis for the criminal conduct of human trafficking in Law Number 21 of 2007 concerning the Crime of Human Trafficking. The disclosure of the case of human trafficking at the coffee shop pangku on Line Two Poros Samarinda-Tenggarong which was carried out directly by the Tenggarong Sebrang police found one of the practices of human trafficking under the guise of a coffee shop, on Line Two Poros Samarinda-Tenggarong. Even though the stalls have been brought under control several times, in reality these stalls are quickly operating again. So it can be seen that law enforcement against the crime of human trafficking under the guise of a coffee shop on Line Two Poros Samarinda-Tenggarong has not been fully running well. The purpose of this study is to determine the enforcement of criminal law against perpetrators of criminal conducts of human trafficking in the Line Two Poros Samarinda-Tenggarong. The two authors want to know the efforts that have been made by the government to overcome the practice of human trafficking in Line Two Poros Samarinda-Tenggarong. Based on the collection of legal data, the authors get answers regarding law enforcement against the perpetrators of the criminal conduct of human trafficking in Line Two Poros Samarinda-Tenggarong, only 1 case was carried out in 2018 against the defendant Wiwik Julianto with an underage victim, in which the defendant was sentenced to 6 years imprisonment. Apart from this case, law enforcement has not been carried out against the perpetrators of the criminal conduct of human trafficking at the coffee shop on Line Two Poros Samarinda-Tenggarong by the Tenggarong Seberang sector police on the grounds that they have not found strong evidence of the existence of human trafficking in the form of prostitution, although they also admit that there are many and still active prostitution activities in the coffee shop. The government's efforts against the practice of human trafficking in the Line Two Poros Samarinda-Tenggarong, efforts by the Satpol PP of Kutai Kartanegara Regency were hampered by field conditions which were indeed protected by community organizations that protected coffee shops on the Line Two Poros Samarinda-Tenggarong and the unpleasant treatment by shopkeepers. The shop is a threat to the safety of its officers. Legal efforts made by the Tenggarong Seberang Police are only limited to data collection, raids on alcohol and arrests traffickers in the form of prostitution only if they receive a report